Trade liberalization and informality in Argentina: exploring the adjustment mechanisms - Guillermo Cruces; Guido Porto; Mariana Viollaz (Latin American Economic Review, 2018)
Abstract This paper studies the link between trade reforms and labor informality in Argentina using a long time series spanning the 1980–2001 period. We explore cross-section mechanisms, that operate at the industry level, and time-series mechanisms, that operate at a general equilibrium level. We argue that firms can substitute formal with informal workers to smooth a negative trade shock. In this setting, industries exposed to larger tariffs cuts could experience increases in informality. In general equilibrium, there can be additional aggregate impacts in both manufacturing and non-traded sectors through workers reallocation among sectors, wage adjustments, and firm entry and exit. Using the cross-section variation of the data and an instrumental variable strategy we explore empirically the cross-section mechanisms. We find that reductions in industry tariffs increase labor informality, and the effect is differentially stronger in industries with a larger share of small-size firms. Using the time-series variation of the data, we are able to identify some of the general equilibrium effects. We find that the fall in the average national tariff decreased aggregate informality in the manufacturing sector but increased it in the non-traded sector.